Changes of terpenoids and other volatiles during alcoholic fermentation of blueberry wines made from two southern highbush cultivars. (July 2019) - Liu, Fangtian; Li, Sunjun; Gao, Jihui; Cheng, Ke; Yuan, Fang
Abstract: Aroma is one of the most important aspects to determine the wine quality and its market value. Changes of volatile profiles and terpenoid precursors were monitored for blueberry wines made from two different southern high bush cultivars (Misty and O'Neal) during the alcoholic fermentation using solid phase microextraction-gas chromatography-quadrupole time of flight-mass spectrometry (SPME-GC-QTOF-MS). Volatile profile of the wine significantly changed as a function of time during fermentation, which was due to the gradual reduction of C6 compounds, extraction and hydrolysis of terpenoids precursors, and generation of esters and alcohols. Misty samples contained higher amount of terpenoids compared to the O'Neal samples during the whole fermentation process. E-asarone and methyl isoeugenol were only detected in O'Neal samples. Myrtenol, E-carveol and borneol were presented mainly as bound form, while other terpenoids mainly as free form in the final wines, indicating the different resistance of the glycoside to acid hydrolysis during fermentation. Highlights: Blueberry cultivar difference remarkably affected the volatile profile of the resulting wines. Fermentation-derived volatiles in wine are mainly associated with the nitrogen level of the blueberries. Terpenoid glycosides have different resistance to acid hydrolysis during fermentation. PCA applied to aroma compounds highlights the differences among fermentation stages.